Earlier Theories of Crises and Cycles in the United States - Miller, Harry E. (Quarterly Journal of Economics, 1924)
I. Theories of the causes of crises and cycles: agnostic theories, 294.—Emphasis placed upon the influence of the credit system, 296.—Attention to the psychology of business men, 299.—Periodicity of commercial crises, 300. — Theory that banks cause the business cycle, 308.—Critics of the theory that banks cause the business cycle, 308. — Theory of the self-generating cycle, 309. — Influence of maladjustments of production, 312. II. Suggestions for moderating the cycle: loan policy, 316.—Variable discount rate, 319.—Surplus reserves at New York, 322.—Abolition of the payment of interest on deposits at New York, 325.—The call-loan evil at New York, 327.